Penerapan metode ceramah dan diskusi dalam pembelajaran pendidikan agama Islam di sekolah - Annisa, Nur; Ivanda, Salsa Bila; Zaman, Nurul (Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe the application of lecture and discussion methods in Islamic Religious Education (IRE) learning in schools. The approach used is library research by reviewing various literature, journals, and previous research results relevant to the topic. The results of the study show that the lecture method is still one of the most effective strategies for delivering conceptual religious material, as it helps teachers explain Islamic values systematically. However, learning that only uses the lecture method tends to be one-way and does not involve student participation. Therefore, the application of the discussion method is an important complement to foster participation, critical thinking, and a deep understanding of IRE material. The combination of these two methods is considered capable of creating an interactive learning atmosphere, increasing motivation, and strengthening students' understanding of spiritual and moral values. Thus, the balanced application of the lecture and discussion methods can increase the effectiveness of PAI learning in schools.